Assisted Reproductive Technology - Deep, JP (Journal of Chitwan Medical College, 2014)
All the treatment or procedure that includes the handling of both human sperm and oocytes or embryos in vitro for the purpose of establishing a pregnancy in order to bypass some pathological obstacles in human reproduction is known as Assisted Reproductive Technology (ART). Now we must be approaching 1.5 million Assisted Reproductive Technology birth since the birth of the world’s first in vitro fertilization baby, Louise Brown, in the United Kingdom. The infertility is caused by various reason and factors from either or both partners. Infertility affects worldwide by 8-15 percent of couples in general and defined as a disease of the reproductive system by the failure to achieve a clinical pregnancy after one year or more of regular unprotected sexual intercourse. DOI: http://dx.doi.org/10.3126/jcmc.v4i1.10840 Journal of Chitwan Medical College 2014; 4(1): 1-10